A multicenter prospective cohort study of endoscopic urethral realignment versus suprapubic cystostomy after complete pelvic fracture urethral injury. Issue 2 (19th February 2023) - McCormick, Benjamin J.; Keihani, Sorena; Hagedorn, Judith; Selph, J. Patrick; Figler, Bradley D.; Johnsen, Niels V.; da Silva, Rodrigo Donalisio; Broghammer, Joshua A.; Gupta, Shubham; Miller, Brandi; Burks, Frank N.; Eswara, Jairam; et al.
Abstract : This is the first prospective multi-institutional study of PFUI. We found no difference in stricture rate between patients treated with primary realignment and SPT with delayed urethroplasty. Abstract : BACKGROUND: Pelvic fracture urethral injury (PFUI) occurs in up to 10% of pelvic fractures. There is mixed evidence supporting early endoscopic urethral realignment (EUR) over suprapubic tube (SPT) placement and delayed urethroplasty. Some studies show decreased urethral obstruction with EUR, while others show few differences. We hypothesized that EUR would reduce the rate of urethral obstruction after PFUI. METHODS: Twenty-six US medical centers contributed patients following either an EUR or SPT protocol from 2015 to 2020. If retrograde cystoscopic catheter placement failed, patients were included and underwent either EUR or SPT placement based on their institution's assigned treatment arm. Endoscopic urethral realignment involved simultaneous antegrade/retrograde cystoscopy to place a catheter across the urethral injury. The primary endpoint was development of urethral obstruction. Fisher's exact test was used to analyze the relationship between PFUI management and development of urethral obstruction. RESULTS: There were 106 patients with PFUI; 69 (65%) had complete urethral disruption and failure of catheter placement with retrograde cystoscopy. Of the 69 patients, there were 37 (54%) and 32 (46%) in the EUR and SPT arms, respectively. Mean age was 37.0 years (SD, 16.3 years) years, and mean follow-up was 463 days (SD, 280 days) from injury. In the EUR arm, 36 patients (97%) developed urethral obstruction compared with 30 patients (94%) in the SPT arm ( p = 0.471). Urethroplasty was performed in 31 (87%) and 29 patients (91%) in the EUR and SPT arms, respectively ( p = 0.784). CONCLUSION: In this prospective multi-institutional study of PFUI, EUR was not associated with a lower rate of urethral obstruction or need for urethroplasty when compared with SPT placement. Given the potential risk of EUR worsening injuries, clinicians should consider SPT placement as initial treatment for PFUI when simple retrograde cystoscopy is not successful in placement of a urethral catheter. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :